The Importance of “Loss and Damage” in Supporting Climate Policy Debate - Tsipouridis, Ioannis; E. Kiprotich, Ngetich; Chebii, Anita Jerotich; Matsagkos, Nektarios; Trachanas, Georgios P. (Technical Annals, 2023)
Climate change is having profound impacts on human and natural systems. In recent years, there has been growing recognition of the need to address Loss and Damage (L&D) associated with the adverse effects of climate change, particularly in developing countries that are more vulnerable to its impacts. There is a range of studies, examining the concepts, resilience, adaptation and policy options for dealing with climate change losses and damages. This article discusses the actions, research and finance needs in Loss & Damage as well as the approaches to it on some topics such as adaptation, stakeholder engagement, governance and risk transfer.